The reception and representation of English as an academic language among foreign students in Poland and its influence on (re)shaping individual identities - Furman, Mateusz; Aleksandrzak, Magdalena (Glottodidactica, 2023)
The article discusses selected problems of learning and using English as an academic language from the perspective of foreign students in Poland. The theoretical part of the paper concentrates on the issues related to the concept of identity and the status of English as an academic lingua franca, especially in the light of the growing role of English for Academic Purposes (EAP) in university education. Such theoretical background is intended to serve as a kind of introduction to the discussion which centres around the influence of this specific social variation of the English language on the process of shaping or reshaping identities among students who have decided to continue their education outside their native language environment in the multilingual context of a university language department. Seen from such a perspective, university courses in EAP may be treated as a form of practical implementation of multilingual pedagogy and, more specifically, the idea of inclusive “classrooms” with a particular goal-oriented curriculum. The empirical part of the article presents the research project which aimed to examine the above-mentioned phenomena as experienced by a group of language students of different ethnic and national background who have been studying (and living) in Poland for at least a year. The main research technique used in this qualitative study was the semi-structured interview, selected with a view to obtaining an in-depth picture and highly personalised account of the process of (re)constructing individual identities in a specific social context and educational setting.